LC-MS/MS-based Quantification of Ten Neurotransmitters in Rat Limbic System and Serum: Application to Chronic Unpredictable Mild Stress- Induced Depression Rats - Mingyan Ma; Qiangxiang Chen; Wen Cao; Yubo Zhou; Aijuan Yan; Yanru Zhu (Mass spectrometry letters, 2023)
As one of the most common mood disorders, numerous studies have shown depression is the main risk factor for non-suicidal self-harm. The pathogenesis of depression is complex, and a comprehensive and rapid measurement of monoamine neurotransmitters and their metabolites will be very helpful in understanding the pathogenesis of depression. Therefore, a rapid and sensitive underivatized liquid chromatography-tandem mass spectrometry method was developed and validated for the simultaneous monitoring of the levels of ten neurotransmitters and their metabolites in rat serum and limbic system and success- fully applied to quantify the changes of neurotransmitter levels in chronic unpredictable mild stress-induced rats. The analytes studied were mainly involved in tyrosine metabolism, tryptophan metabolism, and glutamate cycling pathways, which are important in the pathogenesis of depression. It had been verified the method was sensitive and effective, with satisfactory linear- ity, and met the requirements of biological sample determination. Levels of neurotransmitters in rat serum, hippocampus, amyg- dala, prefrontal cortex, striatum, and hypothalamus were determined via the method. The results showed serotonin, dopamine, norepinephrine, and their metabolites were decreased, glutamine was increased, and glutamate was disturbed in chronic unpre- dictable mild stress-induced depression rats. This method provides a new approach to studying the pathogenesis of depression and other neurological disorders. KCI Citation Count: 0